Standar Pelayanan Aplikasi Bursa Kerja Online pada Dinas Tenaga Kerja Kota Depok - Fauziah, Syifa; Zulmasyhur, Zulmasyhur (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
The Depok government provides Employment application service standards, especially to overcome employment problems in its jurisdiction. However, in practice, there are still minimal critical issues, namely service standards that are not yet optimal. On this basis, this research aims to outline the problems of service standards that require appropriate correction in practice. Then, the method adopted is descriptive qualitative, which attempts to reveal the analysis results systemically and logically based on the content analyzed. The results found were that of the six dimensions analyzed, two of them still did not meet the expected standards, namely service procedures and competency of service providers. Meanwhile, obstacles such as server and network instability and some officers' lack of friendliness hinder the service process. However, four other dimensions are considered to meet the standards well, such as service completion times that meet expectations and no costs charged to the public during the service process.